Test method of in-situ illumination XPS
By using fixed-wavelength lasers to perform cyclic switching light experiments in XPS technology, the challenges of light source stability and environmental control in photocatalytic research are solved, and accurate observation of the dynamic changes of the surface chemical state and electronic structure of the material is achieved, helping to study the photocatalytic reaction mechanism, and reducing the experimental cost.
Patent Information
- Application Number
- CN202510137279.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-05-09
AI Technical Summary
Existing XPS technology has challenges in light source stability, environmental control and result accuracy analysis when studying photocatalytic processes.
A fixed wavelength laser is used as the light source to conduct cyclic switching light experiments, collect the electron energy spectrum data of the sample in real time, analyze the changes in element binding energy, and draw a curve spectrum diagram of the binding energy changes with the light on and off cycles.
Accurate observation of the dynamic changes of the chemical state and electronic structure of the material surface is achieved, helping to study the photocatalytic reaction mechanism, and no hardware development of the equipment is required, saving experimental costs.
Smart Images

Figure CN119959272A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of measuring photoelectron spectra, and in particular to a testing method for in-situ illumination XPS. Background Art
[0002] With the deepening of the research on surface reaction mechanism, the application of in-situ XPS testing method has become increasingly important. In-situ XPS refers to the XPS test performed while the sample is subjected to special treatment such as specific temperature, atmosphere, power or light, so as to achieve real-time observation of the changes in the chemical state of the sample surface. This method provides a powerful characterization method in catalytic reaction research.
[0003] Currently, photocatalysis has gradually become an important research direction to replace traditional thermal catalysis. The photocatalytic process mainly regulates catalytic reactions through two pathways: thermochemical pathway (mainly from visible-near infrared light) and photochemical pathway (mainly from ultraviolet light). Among them, the thermal effect can promote the excitation and separation of carriers in the photochemical process, promote the multi-electron reaction on the surface of the activated catalyst, accelerate the diffusion of the reaction molecules and the desorption of the product molecules; while the photochemical pathway triggers electron transfer through photoelectric excitation, thereby changing the electronic structure of the catalyst surface. In these processes, the changes in the chemical state of the catalyst surface and the adsorption and desorption behaviors can be captured by XPS technology, thereby providing an in-depth understanding of the photocatalytic reaction mechanism. Therefore, the application of in situ illumination XPS is crucial. Existing XPS technology still faces many challenges in studying photocatalytic processes, such as the stability of the light source, the environmental control of the XPS detection chamber (especially the maintenance of high vacuum), and the accuracy of the results. Summary of the invention
[0004] The purpose of this application is to provide an in-situ illumination XPS testing method to accurately reveal the photocatalytic reaction behavior of the material and help study the photocatalytic reaction mechanism. The specific technical solution is as follows:
[0005] The first aspect of the present application provides an in-situ illumination XPS testing method, comprising the following steps:
[0006] (a) Use a laser with a fixed wavelength as the light source, fix the light source, and ensure that the light spot is accurately irradiated on the surface of the test sample;
[0007] (b) Fixing the test sample in the test chamber of the XPS instrument;
[0008] (c) performing cyclic XPS testing in light-on and light-off states to collect electronic energy spectrum data of the test sample in real time;
[0009] (d) performing cyclic repeated testing on the test sample;
[0010] (e) analyzing the electronic energy spectrum data, extracting the change in binding energy of a specific element, and plotting a curve spectrum of the change in binding energy with light-on and light-off cycles.
[0011] In one embodiment of the present application, the test method is performed under high vacuum, and the vacuum degree of the high vacuum is 3×10 -8 Pa and above.
[0012] In one embodiment of the present application, the test method is performed under near-normal pressure, and the pressure range of near-normal pressure is 0.1 mbar-1 bar. Near-normal pressure XPS conditions are an optional means, which is suitable for testing photothermal sensitive samples.
[0013] In one embodiment of the present application, the test atmosphere is selected from an inert gas or a reactive gas, the inert gas is selected from one of argon, nitrogen and helium; the reactive gas is selected from one of CO, H2, CO2 and CH4.
[0014] In one embodiment of the present application, the laser light source is a single wavelength laser with a wavelength range of 320nm-780nm.
[0015] In one embodiment of the present application, the power of the laser is 10 mW-2W.
[0016] In one embodiment of the present application, the diameter of the light spot is 100 μm-3 mm.
[0017] In one embodiment of the present application, two or more laser beams with different wavelengths are used alternately during the test process to analyze the effects of different wavelengths on the electronic structure of the test sample.
[0018] In one embodiment of the present application, the number of cycles of the cyclic repetition test is two or more, and the time of each cycle is 10min-2h, wherein the light-on time is 10min to 1h; the light-off time is 10min to 1h.
[0019] A second aspect of the present application provides a test result, wherein the test result obtained by the test method includes: dynamic changes in the surface composition, content and element valence of the material with light conditions.
[0020] Beneficial effects of this application:
[0021] The present application provides an in-situ illumination XPS test method, which is suitable for studying the dynamic changes of the chemical state and electronic structure of the material surface during the photocatalytic process. The present application uses a laser of a fixed wavelength as an external light source to simulate the photocatalytic reaction conditions. Furthermore, the present application proposes a detection strategy that uses a cyclic switching light experiment to form a cyclic change curve of binding energy, analyzes and verifies the dynamic change of element binding energy with illumination conditions, so as to analyze the chemical state changes of the sample in the illumination experiment and evaluate the light response characteristics of the sample. In addition, according to the needs of different samples, the present application can choose to test on a high vacuum or near-normal pressure XPS instrument, thereby avoiding the misjudgment of the experimental results caused by changes in element binding energy caused by external factors. The test results obtained by the test method of the present application can accurately reveal the true reaction behavior of the material and help study the catalytic reaction mechanism. The present application combines the existing equipment (XPS) and realizes more accurate real-time observation of the changes in the chemical state of the sample surface through the above method, without the need for hardware development of the equipment, saving the cost of the experiment, and having a certain universality for the XPS detection system.
[0022] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0024] Figure 1 The cyclic illumination experiment result of Example 1 of the present application;
[0025] Figure 2 The cyclic illumination experiment result of Example 2 of the present application;
[0026] Figure 3 This is the cyclic illumination experiment result of Example 3 of the present application. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0028] The first aspect of the present application provides an in-situ illumination XPS testing method, comprising the following steps:
[0029] (a) Use a laser with a fixed wavelength as the light source, fix the light source, and ensure that the light spot is accurately irradiated on the surface of the test sample;
[0030] (b) Fixing the test sample in the test chamber of the XPS instrument;
[0031] (c) performing cyclic XPS testing in light-on and light-off states to collect electronic energy spectrum data of the test sample in real time;
[0032] (d) performing cyclic repeated testing on the test sample;
[0033] (e) analyzing the electronic energy spectrum data, extracting the change in binding energy of a specific element, and plotting a curve spectrum of the change in binding energy with light-on and light-off cycles.
[0034] The inventors found that laser is parallel light, and there is basically no problem of light divergence. The light flux of the laser shining on the sample surface is more consistent with the actual reaction, so laser is selected as the external light source. As the light is turned on and off, the curve of the cyclic change of element binding energy. If the element binding energy can be cyclically changed as the light is turned on and off, it can be proved that the effect of light affects the electronic structure of the material. Otherwise, it may be affected by other factors, such as test errors. By using cyclic switching light experiments to analyze and verify the detection strategy of the dynamic change of element binding energy with lighting conditions, the real reaction behavior of the material can be more accurately revealed, which helps to study the mechanism of photocatalytic reaction.
[0035] In this application, the position of the bracket is adjusted and fixed by observing the shape and position of the light spot to ensure that the light spot is stably irradiated on the XPS test area on the sample surface. The bracket can be made of any structurally stable material such as stainless steel, plastic, etc. The bracket is adjustable to ensure that the laser position is variable and stable.
[0036] In the present application, the test sample is selected from one of powder, film or block. The powder sample needs to be pressed into a tablet before testing to ensure that the sample surface is flat. Two or more surface areas of the test sample can be used for XPS testing in sequence.
[0037] In this application, when testing the element fine spectrum, the XPS instrument uses an energy range of 10eV-40eV to ensure good energy resolution.
[0038] In this application, the test conductivity is less than 10 -2 S / cm, the charge neutralization system can be used to neutralize the surface charge to eliminate the surface charge accumulation.
[0039] In one embodiment of the present application, the test method is carried out under high vacuum, and the vacuum degree of the high vacuum is 3×10 -8The inventors have found that accurate results can be obtained by testing light-heat insensitive samples or samples that are stable under high vacuum under high vacuum.
[0040] In one embodiment of the present application, the test method is carried out at near atmospheric pressure, and the pressure range of near atmospheric pressure is 0.1mbar-1bar. Near atmospheric pressure XPS conditions are an optional means, suitable for testing photothermal sensitive samples. For example, it may include but is not limited to Ni2O3, Fe2O3, or CeO2. The inventors have found that choosing to use near atmospheric pressure XPS conditions for XPS testing under illumination can reduce the changes in the chemical state of elements caused by photothermal effects and high vacuum conditions, and can more realistically simulate the actual use environment and reduce the risk of misjudgment.
[0041] In one embodiment of the present application, the test atmosphere is selected to be an inert gas or a reactive gas, which can effectively avoid distortion of the test results caused by the influence of air, water vapor, etc. The inert gas is selected from one of argon, nitrogen and helium; or according to the experimental requirements, the reactive gas is introduced to simulate the real reaction conditions, for example, the reactive gas is selected from one of CO, H2, CO2 and CH4. Among them, the reaction conditions may include light conditions, temperature conditions, etc., which can be adjusted based on different catalytic reactions.
[0042] In one embodiment of the present application, the laser light source is a single wavelength laser with a wavelength range of 320nm-780nm. For example, the wavelength range can be 320nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 780nm or a range consisting of any two of the values. The wavelength of the laser light source is selected according to the different light absorption of the sample at different wavelengths. For example, general TiO2 materials have strong absorption of ultraviolet light and basically no absorption in the visible light region. A light source with a wavelength below 400nm can be selected for experiment. At the same time, a light source in the visible light band can also be used to experiment and compare the changes in the binding energy of the samples under different illumination.
[0043] In one embodiment of the present application, the power of the laser is 10 mW-2 W. For example, the power of the laser can be 10 mW, 20 mW, 50 mW, 100 mW, 200 mW, 500 mW, 800 mW, 2 W, or a range consisting of any two values therein.
[0044] In one embodiment of the present application, the diameter of the light spot is 100 μm-3 mm. Limiting the diameter of the light spot within the scope of the present application can make the light flux per unit area of the sample more appropriate, and a suitable XPS test area can make the test result more accurate.
[0045] In one embodiment of the present application, two or more lasers of different wavelengths are used during the test process to analyze the effects of different wavelengths on the electronic structure of the sample and verify the sample's absorption of light of different wavelengths, i.e., the effects on the electronic structure of the sample.
[0046] In one embodiment of the present application, the number of cycles of the cyclic repetition test is two or more, and the time of each cycle is 10min-2h, wherein the light-on time is 10min to 1h; the light-off time is 10min to 1h.
[0047] The second aspect of the present application provides a test result, and the test results obtained by the test method include: the dynamic changes of material surface composition, content and element valence state with lighting conditions, further revealing the role of light in the catalytic reaction.
[0048] The XPS test operation process of the present application is well known to those skilled in the art and is not particularly limited in the present application.
[0049] Example
[0050] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0051] Test methods and equipment:
[0052] The X-ray photoelectron spectrometer was a Kratos AXIS Supra.
[0053] Example 1
[0054] The bracket is used to fix the laser with a wavelength of 473nm and a power of 1W to ensure that it reaches the Zr-NiCeO x The sample spot is about 2mm diameter circle; Zr-NiCeO x The sample was fixed in the test chamber of a conventional high vacuum XPS instrument, and a cyclic XPS test was performed in the light-on and light-off states; the light-on time was 30 minutes, the light-off time was 30 minutes, and the cycle was repeated twice. The electronic energy spectrum data of the test sample was collected in real time, the electronic energy spectrum data was analyzed, the changes in the binding energy of specific elements were extracted, and the XPS spectrum of the binding energy changing with the light-on and light-off cycles was plotted. Based on the above test, Figure 1 , Figure 1This is the XPS real-time detection result of Example 1 of the present application, where the ordinate is the relative intensity and the normalized reference point is the initial point of the abscissa. The cyclic switching light experiment clearly reveals the phenomenon that the sample is gradually reduced due to thermal effects and high vacuum conditions. The implementation of the cyclic experiment avoids the misjudgment of the experimental results caused by the contingency of a single experiment.
[0055] from Figure 1 It can be seen that as the illumination experiment proceeds, Ni and Ce both show a trend of being reduced, and the analyzed samples have a relatively strong photothermal effect. At this time, the surface temperature of the sample reaches 120°C. In the high vacuum system, the surface O is easily drawn away, causing Ni 0 and Ce 3+ Even after the first illumination experiment ended and the light was turned off, the surface still had a certain temperature and O was still being drawn away. Therefore, Ni 0 and Ce 3+ It is still increasing; in the second light-opening experiment, Ni was almost completely reduced to 0 valence, and Ce also became a more stable Ce 3+ However, from the spectrum of Zr3d, it can be seen that Zr seems to shift to a higher binding energy after the light is turned on. If the cycling experiment is not performed, such a result can easily be misjudged as light-induced electron migration from Zr to Ni and Ce. In fact, the switching light cycling XPS test did not observe dynamic changes in the binding energy of Zr. On the contrary, the sample has undergone irreversible changes under photothermal conditions. In this case, the switching light cycling experiment can avoid the misjudgment of the experimental results due to changes in the binding energy of elements caused by certain external factors, which is of great significance in helping to study the mechanism of photocatalytic reactions.
[0056] Example 2
[0057] Removal of Zr-NiCeO x The samples were placed in the test chamber of the XPS instrument at near atmospheric pressure and the test was carried out in a 1 mbar Ar atmosphere, and the rest was the same as in Example 1. Based on the above test, Figure 2 , Figure 2 This is the characterization result of Example 2 of the present application, where the ordinate is the relative intensity and the normalized reference point is the initial point of the abscissa. The introduction of the atmosphere avoids the phenomenon of sample reduction caused by high vacuum conditions in Example 1, which is closer to the actual photocatalytic reaction process, and the experimental results obtained are more real and reliable.
[0058] from Figure 2It can be seen that in the near-normal pressure XPS test chamber, Ni and Ce of the same sample no longer show the phenomenon of being reduced in the light cycle as in Example 1. At this time, it is more reliable to do the switch light cycle experiment. From Zr3d, it can be observed that light will cause the binding energy of Zr to shift to a lower level by 0.2eV, and this result is reversible in the switch light cycle. This experimental result verifies the dynamic change of element binding energy with light conditions, which can more accurately reveal the true reaction behavior of the material.
[0059] Example 3
[0060] A bracket was used to fix a laser with a wavelength of 405nm and a power of 500mW to ensure that the light spot reaching the Au / SnO2 sample was about 1mm in diameter; the Au / SnO2 sample was fixed in a conventional high vacuum XPS instrument test chamber, and a cyclic XPS test was performed in the light-on and light-off states; the light-on time was 20min, the light-off time was 20min, and the cycle was repeated 3 times. The electronic energy spectrum data of the test sample was collected in real time, the electronic energy spectrum data was analyzed, the changes in the binding energy of specific elements were extracted, and a curve spectrum of the binding energy changing with the light-on and light-off cycles was drawn. Based on the above test, Figure 3 , Figure 3 This is the characterization result of Example 3 of the present application. This result clearly reflects the dynamic electron transfer process of the active metal Au in the sample under light conditions.
[0061] from Figure 3 It can be seen that Au exhibits reversible changes in binding energy in the three-cycle light-on / off experiment. The dynamic response of Au to light can be represented by the cyclic change curve of binding energy. It can be seen from the cyclic curve that under light conditions, the binding energy of Au will move upward by about 0.2 eV, and the binding energy will return to normal after turning off the light. This result can be reproduced in the three-cycle light-on / off experiment. This experimental data makes the evaluation of the light response characteristics of the sample more reliable.
[0062] In summary, this application combines existing equipment (XPS), adds an external light source, and proposes the use of a cyclic switching light experiment to form a cyclic change curve of binding energy, thereby realizing in-situ observation of the sample during the photocatalytic process, and being able to timely track the changes in the electronic information and valence state of each element in the sample. In addition, according to the needs of different samples, this application can choose to test on a high vacuum or near-normal pressure XPS instrument, thereby avoiding changes in element binding energy caused by external factors and causing misjudgment of experimental results. The test results obtained by the test method of this application can accurately reveal the true reaction behavior of the material, which is of great significance for the exploration of the reaction mechanism of photocatalysis. This application can be implemented without the need to modify and develop the software and hardware of the XPS system on the existing basis, and has the advantages of low cost and easy operation.
[0063] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A method for testing in-situ illumination XPS, comprising the following steps: (a) Use a laser with a fixed wavelength as the light source, fix the light source, and ensure that the light spot is accurately irradiated on the surface of the test sample; (b) Fixing the test sample in the test chamber of the XPS instrument; (c) performing cyclic XPS testing in light-on and light-off states to collect electronic energy spectrum data of the test sample in real time; (d) performing cyclic repeated testing on the test sample; (e) analyzing the electronic energy spectrum data, extracting the change in binding energy of a specific element, and drawing a curve spectrum of the change in the binding energy of the element with light-on and light-off cycles.
2. The testing method according to claim 1, wherein: The test method is carried out under high vacuum, and the vacuum degree of the high vacuum is 3×10 -8 Pa and above.
3. The testing method according to claim 1, wherein: The test method is carried out under near-normal pressure, and the pressure range of the near-normal pressure is 0.1 mbar-1 bar.
4. The testing method according to claim 1, wherein: The test atmosphere is selected from an inert gas or a reactive gas, wherein the inert gas is selected from one of argon, nitrogen and helium; and the reactive gas is selected from one of CO, H2, CO2 and CH4.
5. The testing method according to claim 1, wherein: The laser light source is a single-wavelength laser with a wavelength range of 320nm-780nm.
6. The testing method according to claim 1, wherein: The power of the laser is 10mW-2W.
7. The testing method according to claim 1, wherein: The diameter of the light spot is 100 μm-3 mm.
8. The testing method according to claim 1, wherein: During the test, two or more laser beams with different wavelengths are used alternately to analyze the effects of different wavelengths on the electronic structure of the test sample.
9. The testing method according to claim 1, wherein: The number of cycles of the cyclic repetition test is two or more, and the time of each cycle is 10min-2h, wherein the light-on time is 10min to 1h; the light-off time is 10min to 1h.
10. The testing method according to claim 1, wherein: The test results obtained by the test method include: dynamic changes of material surface composition, content and element valence state with light conditions.